2008
DOI: 10.1002/hep.22180
|View full text |Cite
|
Sign up to set email alerts
|

The role of Hfe in transferrin-bound iron uptake by hepatocytes

Abstract: HFE-related hereditary hemochromatosis results in hepatic iron overload. Hepatocytes acquire transferrin-bound iron via transferrin receptor (Tfr) 1 and Tfr1-independent pathways (possibly Tfr2-mediated). In this study, the role of Hfe in the regulation of hepatic transferrin-bound iron uptake by these pathways was investigated using Hfe knockout mice. Iron and transferrin uptake by hepatocytes from Hfe knockout, non-iron-loaded and iron-loaded wild-type mice were measured after incubation with 50 nM 125 I-Tf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
3
15
2
Order By: Relevance
“…Taken together, these observations make it clear that TFR1 is the dominant TFR involved in iron uptake in hepatoma cells. Furthermore, we showed that cells treated with both TFR1 and TFR2 siRNA did not exhibit impaired iron uptake at a high transferrin concentration, providing support for the existence of a TFR-independent pathway in hepatoma cells which involves the low-affinity endocytosis of transferrin as described previously in hepatocytes (9).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Taken together, these observations make it clear that TFR1 is the dominant TFR involved in iron uptake in hepatoma cells. Furthermore, we showed that cells treated with both TFR1 and TFR2 siRNA did not exhibit impaired iron uptake at a high transferrin concentration, providing support for the existence of a TFR-independent pathway in hepatoma cells which involves the low-affinity endocytosis of transferrin as described previously in hepatocytes (9).…”
Section: Discussionsupporting
confidence: 84%
“…Human apotransferrin was labeled with 57 CoCl2 (Perkin Elmer) as detailed above for unlabeled Co2Tf. TFR1-mediated uptake of Fe2Tf was measured at a transferrin concentration of 50 nM, and TFR1-independent uptake (putative TFR2 pathway) was measured at a transferrin concentration of 5 M, as described previously (9,28). Uptake of Co 2Tf was measured at the same concentrations as Fe2Tf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocytes and hepatoma cells are known to take up Fe-TF by several mechanisms including a high affinity, low capacity TFR1-mediated endocytic pathway and a low affinity, high capacity TFR1-independent pathway (28 -31). In primary mouse hepatocytes and HuH7 hepatoma cells, the TFR1-mediated pathway saturates at low TF concentrations between 50 and 100 nM (31,32). Here, we document that in HepG2 cells incubated with 100 nM TF, knockdown of endogenous ZIP14-FLAG resulted in 45% less assimilation of iron from TF compared with controls.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies showed that Hfe competes with Tf for the same binding sites on Tfrc, thereby impairing iron uptake. [16][17][18][19] Yet, despite all of the studies describing interaction of Hfe with Tfrc, [19][20][21] few investigated their association within the erythroid compartment, where the latter is known to be essential. 22 Earlier studies reported that Hfe could not be detected in nucleated erythroid cells 23 and that liver-specific ablation of Hfe mirrors most of the HH phenotype, indicating that it plays a pivotal role in this organ.…”
Section: Introductionmentioning
confidence: 99%